2014
DOI: 10.1038/srep05587
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum polysaccharides therapeutically improve hepatic functions in non-alcoholic steatohepatitis rats and cellular steatosis model

Abstract: This study aimed to investigate the possible therapeutic effects and active components of Lycium barbarum polysaccharides (LBP) on a high fat diet-induced NASH rat model. We induced NASH in a rat model by voluntary oral feeding with a high-fat diet ad libitum for 8 weeks. After 8 weeks, 1 mg/kg LBP was orally administered for another 4 weeks with a high-fat diet. When compared with NASH rats treated for 12 weeks, therapeutic LBP treatment for 4 weeks during 12 weeks of NASH induction showed ameliorative effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 43 publications
5
79
0
Order By: Relevance
“…Apricot is a fruit that has a high content of carotenoids, mostly β-carotene, and its supplement alleviates oxidative stress and SS induced by carbon tetrachloride in mice [24]. The administration of Lycium barbarum polysaccharides has been shown to ameliorate he- patic SS, inflammation, oxidative stress, and fibrosis in NASH mice [25].…”
Section: Discussionmentioning
confidence: 99%
“…Apricot is a fruit that has a high content of carotenoids, mostly β-carotene, and its supplement alleviates oxidative stress and SS induced by carbon tetrachloride in mice [24]. The administration of Lycium barbarum polysaccharides has been shown to ameliorate he- patic SS, inflammation, oxidative stress, and fibrosis in NASH mice [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that LBP ameliorates dyslipidemia, promotes energy expenditure and reduces body weight, improving nonalcoholic steatohepatitis45. Our previous studies demonstrated that dysfunction of hepatic energy signalling induced by high-fat diet (HFD) represents a key mechanism for hepatic insulin resistance and lipid accumulation associated with nonalcoholic fatty liver disease (NAFLD).…”
mentioning
confidence: 99%
“…Therefore, L. barbarum has been widely cultivated in different regions of China such as Qinghai, Xinjiang, Inner Mongolia, Hebei, Shanxi, Zhejiang, and Gansu. Generally, polysaccharides are considered as one of main bioactive components in the fruit of L. barbarum, which possess a range of biological activities (Amagase and Farnsworth, 2011;Jin, Huang, Zhao, & Shang, 2013;Lin, Wang, Chang, Inbaraj, & Chen, 2009;Potterat, 2010;Xiao et al, 2014). Indeed, the bioactivities of polysaccharides are closely correlated to their chemical structures such as compositional monosaccharides and glycosidic linkages (Hu, Cheong, Zhao, & Li, 2013;Li, Wu, Lv, & Zhao, 2013 Mongolia, and Gansu, have seldom been compared with those of L. barbarum produced in Ningxia (the officially authentic L. barbarum) due to the structural complicity and macromolecular masses of polysaccharides .…”
mentioning
confidence: 99%